Monitoring of microscopic filamentous fungi in indoor air of transplant unit - Holý, Ondřej; Matoušková, Ivanka; Kubátová, Alena; Hamal, Petr; Svobodová, Lucie; Sedlatá Jurásková, Eva; Raida, Luděk (Central European Journal of Public Health, 2015)
AIM: The aim of the study was to control the microbial contamination of indoor air monitored monthly at the Transplant Unit of the University Hospital Olomouc from August 2010 to July 2011. METHODS: The unit is equipped with a three-stage air filtration system with HEPA filters. The MAS-100 air sampler (Merck, GER) was used. Twenty locations were singled out for the purposes of collecting a total of 720 samplings of the indoor air. Swabs of the HVAC diffusers at the sampling locations were always carried out after the sampling of the indoor air. RESULTS: In total, 480 samples of the indoor air were taken for Sabouraud chloramphenicol agar. In 11 cases (2.29%) the cultivation verified the presence of microscopic filamentous fungi. Only two cases involved the sanitary facilities of a patient isolation box; the other positive findings were from the facilities. The most frequent established genus was Aspergillus spp. (4x), followed by Trichoderma spp. (2x) and Penicillium spp. (2x), Paecilomyces spp., Eurotium spp., and Chrysonilia spp. (1x each). In 2 cases the cultivation established sterile aerial mycelium, unfortunately no further identification was possible. A total of 726 swabs of HVAC diffusers were collected (2 positive-0.28%). The study results demonstrated the efficacy of the HVAC equipment. CONCLUSIONS: With the continuing increase in the number of severely immunocompromised patients, hospitals are faced with the growing problem of invasive aspergillosis and other opportunistic infections. Preventive monitoring of microbial air contaminants is of major importance for the control of invasive aspergillosis.
Keywords: Air Microbiology; infekce spojené se zdravotní péčí; Air Pollution, Indoor; jednotky nemocniční; Immunosuppression Therapy; Cross Infection; Fungi; Hospital Units; nemocnice univerzitní; znečištění vzduchu ve vnitřním prostředí; Hospitals, University; mikrobiologie vzduchu; transplantace; imunosupresivní léčba; houby; Environmental Monitoring; monitorování životního prostředí; Transplantation